Altiplano F2007, new wheat variety for seasonal plantings - Villaseñor Mir Héctor Eduardo; Huerta Espino, Julio; Espitia Rangel, Eduardo; Solís Moya Ernesto; Osorio Alcalá Leodegario; Ireta Moreno, Javier; Pérez Herrera Patricia (Revista Mexicana de Ciencias Agrícolas, 2018)
The variety Altiplano F2007 was generated by the Wheat Genetic Improvement Program of the INIFAP based in the Experimental Field Valley of Mexico. It is a variety of spring habit which was obtained from a single cross and the application of the method of selection massive families. Porte semi-erect and has to be tillering tolerant to lodging stalks. In early tasseling has a high frequency of plants with recurved f lag leaf. At maturity its ears are light, pyramidal, loose and slightly curved position color. It is intermediate sized plant and cultivation cycle intermediate late. It is resistant to moderately resistant to leaf rust and stripe rust, and tolerant to foliar diseases complex. From 2005 to 2012 he experimented on 121 different sites at critical time (less than 300 mm), intermediate (300 to 600 mm) and favorable (over 600 mm), and the three conditions surpassed the nine control varieties of 7% up to 24%, with more intermediate seasonal advantage. It is a variety that performs consistently as the production environment is better. Its grain is medium, medium-hard, white to amber color, high test weight, strong gluten, balanced and with good bread volume, so it is classified in group 1 wheat, which is suitable for machine industry in the development of packaged bread or bread type roll, but is also suitable for mixing and correct soft wheat gluten or are tenacious. It is recommended for planting in all wheat growing areas of seasonal plantings in early to intermediate.